The Origin and Evolution of an Anomalous Academic Credential: The Ontario College Advanced Diploma - Skolnik, Michael (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2023)
The Ontario College Advanced Diploma requires three years of post-secondary education and the attainment of learning outcomes like those of a three-year baccalaureate degree. Except for one other Canadian province, no similar academic credential is awarded by colleges in Canada or the United States. For these reasons it has been viewed by some as an anomalous academic credential. This article relates how Ontario colleges came to offer such a rare credential and how the credential survived for over half a century. Employing the concept of path dependence, the origins of the advanced diploma are traced back to the institutes of technology that were first established in Ontario in the 1940s. The article employs a mix of historical inquiry, document analysis, enrolment trend analysis, and literature review methodologies.